Clinical-immunohistochemical characteristics of atypical endometrial hyperplasia in women of reproductive age. - I. B. Vovk; T. D. Zadorozhnaya; N. E. Gorban; V. K. Kondratiuk (Medičnì Perspektivi)
The article presents the analysis of clinical-morphological and immunohistochemical features of endometrial hyperplasia. 60 patients of reproductive age with non-atypical endometrial hyperplasia (EH) were examined. The following morphological distribution of its different types was established: glandular – 56.6%, glandular-cystic – 40.0%, stromal and cystic-atrophic forms  – 1.7%, respectively. When carrying out immunohistochemical studies, the expression of CD-138, a modern reliable marker of the presence of an inflammatory process in endometrial tissue was determined. In the group with non-atypical glandular EH, signs of the inflammatory process in the endometrium were verified in 7 (20.59%) patients. In the group with signs of glandular-cystic change of EH – in 11 (45,83%) patients, as well as in the only patient with non-atypical stromal EH (100,0%). In almost one-third of patients with different morphological types of EH in 19 (31.7%) of 60 the presence of structural-morphological signs of chronic endometritis was revealed, which was manifested by signs of lymphoplasmacytic infiltration, indicating the presence of chronic inflammatory process. These data indicate the possible pathogenetic role of inflammation as one of the trigger factors for the hyperplastic transformation of endometrial structures, which allows to confirm the role of infectious factors in the occurrence of these processes in almost one third of patients with non-atypical ЕН. Thus, the conducted studies indicate that the development of EН is a process based on both the infectious factor and hormonal metabolic disorders, which dictates different personalized approaches to therapeutic tactics.